PRINCIPALS’ PERFORMANCE IN SOUTH SUMATERA PROVINCE, INDONESIA - Dwi Priyono (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this research is to study the extent of correlation between self-concept, empathy, and emotional intelligence with the principals‟ performance. The research relied on survey method by using correlation technique. The population is the principals of the public Senior High Schools in the South Sumatera Province. The result shows:1) there is a positive correlation between self-concept and the principals‟ performance by correlation coefficient ry1= 0,451 and the equation of simple linier regression = 8,188 + 0,970X1; 2) there is a positive correlation between empathy and the principal‟s performance by correlation coefficient ry2 = 0,685 accounted variance r2 y1 = 0.469 and the equation of simple linier regression = 36, 352 + 0.695x2.; 3) there is positive correlation between emotional intelligence and the principals‟ performance by correlation coefficient ry3 = 0,685 accounted variance r2 y3 = 0,469 and the equation of simple linier regression = 30,752 + 0,775x3. ; 4) there is a positive correlation between there predicator variables and the principals‟ performance by correlation coefficient ry.123 = 0,748 accounted variance r2 y.123 = 0,560 and the equation of simple linier regression = 33, 172 + 0,003X1 + 0,297X2+ 0,441X3. All the testing were at = 0.001 level of significance.